2006
DOI: 10.1109/tap.2006.874364
|View full text |Cite
|
Sign up to set email alerts
|

A Perturbed E-Shaped Patch Antenna for Wideband WLAN Applications

Abstract: A wideband -shaped microstrip patch antenna for wireless communications is presented. Zig-zag slots and perturbations of the -shaped metallic patch are employed to excite two resonant modes and achieve a wide-band frequency behavior, featuring a fractional bandwidth of about 30%, and, at the same time, to meet the occupation volume requirements of mobile wireless local-area network enabled communication devices. A locally conformal finite-difference time-domain numerical procedure has been employed to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 15 publications
(15 reference statements)
0
40
0
Order By: Relevance
“…For this reason, the adoption of Cartesian meshes could result in reduced numerical accuracy when structures having curved boundaries have to be modelled. In this case, locally conformal FDTD schemes [1], [2] provide clear advantages over the use of the stair-casing approach or unstructured and stretched space lattices, potentially suffering from significant numerical dispersion and/or instability [19]. Such schemes, necessary to improve the numerical accuracy of the conventional algorithm, are based on the definition of effective material parameters suitable to describe the geometrical and electrical characteristics of the structure under analysis.…”
Section: Locally Conformal Finite-difference Time-domain Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the adoption of Cartesian meshes could result in reduced numerical accuracy when structures having curved boundaries have to be modelled. In this case, locally conformal FDTD schemes [1], [2] provide clear advantages over the use of the stair-casing approach or unstructured and stretched space lattices, potentially suffering from significant numerical dispersion and/or instability [19]. Such schemes, necessary to improve the numerical accuracy of the conventional algorithm, are based on the definition of effective material parameters suitable to describe the geometrical and electrical characteristics of the structure under analysis.…”
Section: Locally Conformal Finite-difference Time-domain Techniquementioning
confidence: 99%
“…In the considered antenna configuration, dipole #1 is driven by a delta-gap voltage source with internal resistance 1 300 G RR   , whereas dipole #2 is closed on a matched load having resistance 2 LG RRR . To properly enlarge the antenna bandwidth, thus reducing latetime ringing phenomena, a continuous resistive loading, having Wu-King-like profile [3], [15], [16]: …”
Section: The Full-wave Antenna Modellingmentioning
confidence: 99%
“…Researchers have offered numerous techniques for bandwidth enhancement of microstrip patch antennas to support multiple wireless communication systems using single antenna. These techniques include use of shorting pin [5], aperture coupling [6], stacked patch [7], staggering effect [8], modified feed [9], thick foam substrate [10], fractal slots [11], PBG structure [12], and slots on the radiating patch [13] to enhance the bandwidth of microstrip antennas. The combinations of radiating patch and the ground plane slots [14] were also analyzed to achieve compact broadband operation.…”
Section: Introductionmentioning
confidence: 99%
“…Tyagi and Vyas [12] designed a slotted Ushaped microstrip antenna with PBG structure which has an impedance bandwidth of 35%. Diego et al [13] designed a wide band E shaped patch antenna that provides an impedance bandwidth of about 29.8% by cutting a zigzag slot on the patch. Kaur et al [14] has designed a U-shaped slot loaded inverted circular patch antenna with maximum bandwidth of 24.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Diego et al demonstrated a wide band E-shaped patch antenna on a low dielectric substrate of thickness 0.061λ 0 (where λ 0 is the freespace wavelength at the central operating frequency) that enables an impedance bandwidth of about 29.8% by cutting a zigzag slot in the patch [9]. Gh.…”
Section: Introductionmentioning
confidence: 99%